Postponed surgery of an acute aortic dissection (type A) in a Jehovah’s Witness with significant hemostatic disorders - Biskupski, Andrzej; Waligórski, Szymon; Mokrzycki, Krzysztof; Brykczyński, Mirosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
In this case report, we present the treatment of an acute type A aortic dissection in a Jehovah’s Witness patient. In accordance with the will of the patient, blood products were not used. Additionally, the patient had significant hemostatic disorders due to the use of antiplatelet drugs.